Twin-roll casting of wire of magnesium alloys - Kaden, Christoph; Kittner, Kristina; Ullmann, Madlen; Prahl, Ulrich (Frontiers in Metals and Alloys, 2025)
Twin-roll casting (TRC) enables the production of near-net-shape semi-finished products in a single forming step, offering significant energy and cost savings compared to conventional rolling. While TRC has been successfully applied to flat magnesium alloy products, its application to long products, such as wires, remains a novel research focus. In this study, the microstructure, texture, and mechanical properties of TRC wires were investigated for the common wrought alloys AZ31 and AZ80, as well as the calcium-containing alloy ZAX210. Microstructural analysis was performed using scanning electron microscopy (SEM) and electron backscatter diffraction (EBSD). Mechanical properties were evaluated through tensile testing at room temperature. The TRC wires exhibited a central segregation zone with a characteristic necklace-like grain structure composed of small and large grains. The addition of Ca in ZAX210 significantly reduced segregation. SEM analysis revealed fine and large network-like intermetallic phases, including Mg17Al12, AlMn, and Ca2Mg6Zn3. Texture analysis indicated a pole split or a shifted basal pole with low intensities. Tensile testing showed that the increased Al content in AZ80 led to lower mechanical properties compared to AZ31. Both alloys displayed low elongation at fracture due to pronounced central segregation and brittle intermetallic phases. In contrast, ZAX210 exhibited a finer and more homogeneous microstructure, resulting in the highest tensile strength and elongation at fracture. These findings suggest that the TRC process introduces characteristic microstructural features that influence mechanical properties. The observed improvements in ZAX210 highlight the potential of calcium additions to refine the microstructure and mitigate segregation effects.